Sosialisasi Penyajian Dan Pembuatan Laporan Sesuai PSAK 45 Di SDN 11 Lenteng Agung - Puspa Rini; Kampono Imam Yulianto; Indra Setiawan; Devvy Noveliza; Mayasari Mayasari; Dias Adi Dharma (Lembaga Penelitian Dan Pengabdian Pada Masyarakat (LPPM) Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2020)
In order to community service, IBI Kosgoro 1957 seeks to help the problems faced by community groups. This form of community service is socialization of presentation and creation of reports in accordance with PSAK 45 in 2019. The presentation of The Responsibility report or more familiarly known as SPJ / LPJ is generally part of the relevant school financial statements, the presentation of an activity information data that has been carried out, with the reporting of implementation indicators recording every income and financial related expenses sourced from the school's operational assistance fund. As an operator, school or administrative management team on the accountability report, of course it is obligatory to be able to make a report in an accountable and transparent manner. Related to that, the importance of socialization towards the presentation of accountability report refers to psak 45 non-profit institutions that we socialize to assist the treasurer or administrator in carrying out his duties in the school, whether at the elementary, junior high, high school or vocational school level. Keywords: Socialization, Presentation and creation of Report, PSAK 45